Jaringan Syaraf Tiruan Untuk Memprediksi Jumlah Permintaan Pemasangan Indihome Dengan Metode Backpropagation - Etca Adetina Banurea (STMIK Budi Darma, 2019)
Branch artificial neural networks of artificial intelligence that mimic or imitate the workings of the human brain. ANN can be implemented in various applications to solve many problems, especially in the field of forecasting. One algorithm that is often used is Bacpropagation. Backpropagation is an algorithm that can be used to predict the number of Indihome installation requests. There are two stages used in the backpropagation method, namely the training stage and the testing phase. In the training phase the pattern tries to recognize the input and at the testing stage the recognizable pattern is tested so that it is known the network pattern that can recognize and predict the number of indihome installation requests. The number of requests for Indihome installation is one. In this study the artificial neural network method is used backpropagtion method for predicting the number of individual installation requests. The software used for testing is the Matlab version 6.1 application.